THE RESURGENCE OF JINGDEZHEN CERAMIC ART: AN ANALYSIS OF INFLUENTIAL FACTORS - Chen Jiasong; Dahlan Abdul Ghani (Journal of Islamic, Social, Economics and Development, 2024)
The resurgence of Jingdezhen Ceramic Art, a cherished cultural heritage of China, is influenced by a multitude of factors that intersect art, culture, and economics. This research aims to investigate these factors and their impact on revitalizing Jingdezhen Ceramic Art, shedding light on the challenges and opportunities facing this historic art form. In the 21st century, Jingdezhen has actively repositioned its ceramic industry by integrating traditional ceramic art with daily-use ceramics, creating a unique blend of art and functionality. This transformation aligns with the global trend of merging arts and business, where culture becomes a brand and an economic driver. However, despite its rich history and cultural significance, contemporary ceramic handicrafts in Jingdezhen face challenges related to originality in design and creativity. This study seeks to explore the influence of cultural heritage, production methods, decorative design elements, and modern design characteristics on the resurgence of Jingdezhen Ceramic Art. Qualitative research, including in-depth interviews with key stakeholders in the industry, will be conducted to gain insights into these factors. By delving into the perspectives of ceramic artists, manufacturers, dealers, collectors, and academics, this research aims to provide a comprehensive understanding of the dynamics at play in the resurgence of this treasured art form.